2007
DOI: 10.1007/s00421-007-0530-8
|View full text |Cite
|
Sign up to set email alerts
|

Low agreement of ventilatory threshold between training modes in cardiac patients

Abstract: In cardiac rehabilitation, different endurance exercises such as walking and cycling are often performed. The training intensity for these modes is determined from a single treadmill or bicycle test by ventilatory threshold (VT). In this study, differences of VT between walking and cycling and agreement of VT between training modes were assessed in cardiac patients. A total of 46 cardiac rehabilitation patients (mean age 59.5+/-8.4 years, 45 males) (31 untrained and 15 trained) completed a maximal exercise tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…Additionally, the mode used for CPX, typically a treadmill or lower-extremity ergometer, potentially impacts the VT response for a given individual. 37 Therefore, when VT is used to prescribe exercise intensity, the same mode should be used for both testing and training, as discussed further in the section on Exercise Prescription. Exercise training has been shown to increase V O 2 at the VT to a degree that is similar to that for peak or maximal V O 2 (typically 10% to 25% for previously sedentary individuals); thus, it is an important response to document clinically.…”
Section: Ventilatory Thresholdmentioning
confidence: 99%
“…Additionally, the mode used for CPX, typically a treadmill or lower-extremity ergometer, potentially impacts the VT response for a given individual. 37 Therefore, when VT is used to prescribe exercise intensity, the same mode should be used for both testing and training, as discussed further in the section on Exercise Prescription. Exercise training has been shown to increase V O 2 at the VT to a degree that is similar to that for peak or maximal V O 2 (typically 10% to 25% for previously sedentary individuals); thus, it is an important response to document clinically.…”
Section: Ventilatory Thresholdmentioning
confidence: 99%
“…and disease have reported that the V O 2 at the anaerobic (AT) or ventilatory (T vent ) threshold is significantly higher when incremental exercise testing is performed on a treadmill than on a cycle ergometer [9,12,15,18,19,23,25,30,32,43]. These Relationship between exercise-induced decreases (Δ) in plasma bicarbonate (HCO 3 -) concentrations and increases in the ventilation above and beyond that needed to support any given increment in oxygen uptake (i.e., excess ventilation) during submaximal and maximal exercise on a cycle ergometer and treadmill.…”
Section: 32b Ventilatory (Anaerobic) Threshold Numerous Studies mentioning
confidence: 99%
“…was calculated [13] by V-slope method, as executed in previous studies from our laboratory [14]. Ventilatory threshold is used to estimate the anaerobic threshold, which is the exercise intensity at which lactic acid starts to accumulate in the circulation (as a result of anaerobic metabolism).…”
Section: Physical Fitness Tests Cardiopulmonary Exercise Capacitymentioning
confidence: 99%